African Elephant Specialist Group meeting May 27th to June 1st, 1994: working group recommendations [Mombasa, Kenya] - Elephant African (Pachyderm)
Two main working groups, one focused on human-elephant conflict and the other on trade and illegal hunting, were convened and each divided into sub-groups to discuss specific aspects of the theme. The human/elephant conflict group had four sub-groups, one reviewed physical barriers and deterrents, one assessed involvement of local communities, one looked at the methods to deal with problem animals, and the last reviewed methods of evaluating and assessing damage to life and property. The trade and illegal hunting working group had two sub-groups, one looked at trade in elephant products and ivory stockpiles while the second one reviewed the monitoring of illegal killing of elephants. Results of the discussion are summarized with much of the material in the first three sub-groups from the human-elephant conflict group presented in tabular form.